Analysis of the Implementation of Muamalah Principles in the Operations of a Sharia Hotel (Case Study at Savindra Residence) - Muhammad Ali Fikri; Muhammad Iqbal Maulana; Hana Putri H; Jaenudin J; Dian Herdiana (Media Hukum Indonesia (MHI), 2026)
This study examines how muamalah principles are implemented in the daily operations of a sharia hotel in Indonesia. Using a qualitative descriptive-analytic approach, data were collected through interviews, observations, and literature reviews, including DSN-MUI Fatwa No.108/2016. The findings show that the hotel applies sharia-compliant service contracts by strictly verifying marital status, preventing unlawful activities, and ensuring transparency in every transaction. Ethical values such as amanah and ihsan are reflected in the staff’s polite yet firm attitude when communicating rules to guests. However, challenges remain, including limited guest understanding of sharia regulations, insufficient supporting facilities, and occasional security issues. The study concludes that although the hotel has generally upheld muamalah principles, improvements in guest education and sharia-based facilities are still needed for more optimal implementation